Frequency, prevalence, incidence and risk factors associated with visual hallucinations in a sample of patients with Parkinson's disease: a longitudinal 4‐year study. (28th August 2012) - Gibson, G.; Mottram, P. G.; Burn, D. J.; Hindle, J. V.; Landau, S.; Samuel, M.; Hurt, C. S.; Brown, R. G.; M Wilson, K. C.
Abstract : Objective: To examine the prevalence, incidence and risk factors associated with visual hallucinations (VHs) amongst people suffering from Parkinson's disease (PD). Methods: We recruited 513 patients with PD from movement disorder and PD clinics within three sites in the UK. Patients were interviewed using a series of standardised clinical rating scales at baseline, 12, 24 and 36 months. Data relating to VHs were collected using the North‐East Visual Hallucinations Interview. Prevalence rates for VHs at each assessment were recorded. Associations were determined using multiple regression analysis. Results: Cross‐sectional prevalence rates for VHs at baseline, 12, 24 and 36 months indicated VHs in approximately 50% of patients. A cumulative frequency of 82.7% of cases at the end of the study period exhibited VHs. The incidence rate for VHs was 457 cases per 1000 population. Longer disease duration, greater impairment in activities of daily living and higher rates of anxiety were most commonly associated with VHs. No factors predictive of VHs could be ascertained. Conclusions: When examined longitudinally, VHs affect more patients than is commonly assumed in cross‐sectional prevalence studies. Clinicians should routinely screen for VHs throughout the disease course. Disease duration, impairment in activities of daily living and anxiety presented as co‐morbidities associated with VHs in PD, and therefore those presenting with VHs should be screened for anxiety disorder and vice versa. Copyright © 2012 John Wiley & Sons, Ltd.